2019
DOI: 10.3390/rs11030360
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability of Precipitation and Biomass of Alpine Grasslands on the Northern Tibetan Plateau

Abstract: The timing regimes of precipitation can exert profound impacts on grassland ecosystems. However, it is still unclear how the peak aboveground biomass (AGBpeak) of alpine grasslands responds to the temporal variability of growing season precipitation (GSP) on the northern Tibetan Plateau. Here, the temporal variability of precipitation was defined as the number and intensity of precipitation events as well as the time interval between consecutive precipitation events. We conducted annual field measurements of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 82 publications
1
25
0
Order By: Relevance
“…Our result is in line with previous studies showing that grasslands in drier and warmer regions are highly sensitive to precipitation (Li et al, 2019a). Li et al (2019b) also suggested that desert steppes are likely to have high sensitivity to the timing variability of precipitation on the Northern Tibetan Plateau. One potential explanation is that desert steppes are always characterized by poor species and low vegetation productivity due to low precipitation (Wu, Shen & Zhang, 2014), but with high precipitation variation which can result in rapid changes in the key carbon cycle process (Knapp et al, 2002).…”
Section: The Spatial Pattern Of Grassland Vulnerabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…Our result is in line with previous studies showing that grasslands in drier and warmer regions are highly sensitive to precipitation (Li et al, 2019a). Li et al (2019b) also suggested that desert steppes are likely to have high sensitivity to the timing variability of precipitation on the Northern Tibetan Plateau. One potential explanation is that desert steppes are always characterized by poor species and low vegetation productivity due to low precipitation (Wu, Shen & Zhang, 2014), but with high precipitation variation which can result in rapid changes in the key carbon cycle process (Knapp et al, 2002).…”
Section: The Spatial Pattern Of Grassland Vulnerabilitysupporting
confidence: 93%
“…ANUSPLIN is a professional interpolation software in which one or more influence factors can be included as covariates to improve the interpolation accuracy, especially for time series of meteorological data (Hutchinson, 2004). Our previous studies have shown the accuracy of interpolation data (Chen et al, 2014;Li et al, 2019b).…”
Section: Data Collectionmentioning
confidence: 98%
“…Previous studies [6,51,60,61] have reported the rising river flows due to glacier retreat in the HKHT regions. However, our results showed that the river flows and GMC fluctuations have no consistent trends but rather they are mainly controlled by the changing climate, especially the precipitation (despite the significant differences in precipitation patterns over basins and catchments) [44]. In the rainfall-runoff-dominated HKHT Interior and Yellow River basin, the insufficient precipitation has derived two contradictory trends: Increased GMC but decreased flows and shrinking lakes in the same period.…”
Section: Discussionmentioning
confidence: 56%
“…The causes of lake fluctuation remain tangled due to elusive precipitation trends in the high-altitude regions [43,44]. The data indicates that temperature increases (0.1~0.6 per decade) in the HKHT regions are more pronounced compared to the lower elevation regions [1,45], thus leading to a rapid retreat of glaciers in recent decades [3,46].…”
Section: Possible Causes Of Lake Fluctuationmentioning
confidence: 99%
“…Based on the NDVI data from 1982 to 2014, an advancing start of growing season, delayed end of season and increasing length of growing season were identified for meadow areas in the eastern TP; while the opposite changes were found for the steppe and sparse herbaceous or sparse shrub areas in the northwest and western edges of the TP. The satellite-observed phenology changes were driven by a number of environmental factors including temperature [281][282][283], precipitation [284], sunshine duration [285], and snow cover [286]; and may be partially attributed to aerosol contamination in the satellite observations [287].…”
Section: Tibetan Plateaumentioning
confidence: 99%